miR-497-5p inhibits gastric cancer cell proliferation and growth through targeting PDK3 - Feng, Lan; Cheng, Kai; Zang, Rongjia; Wang, Qingdong; Wang, Jianjie (Bioscience reports, 2019)
MicroRNA plays an important role in gastric cancer (GC) development, while the function of miR-497-5p in this disease remains unknown. In the present study, we demonstrated miR-497-5p as a tumor suppressive microRNA in GC. miR-497-5p was down-regulated in GC tissues and its expression was associated with the disease stage. Inhibition of miR-497-5p promoted GC cell proliferation and growth. By contrast, miR-497-5p ectopic expression suppressed the proliferation and growth of GC cells. In addition, miR-497-5p inhibited DNA synthesis and enhanced apoptosis in GC cells. The cell cycle progression was suppressed by miR-497-5p. Mechanistically, miR-497-5p directly targeted and suppressed the expression of pyruvate dehydrogenase kinase 3 (PDK3), which is highly expressed in GC tissues. Over-expression of PDK3 promoted the proliferation of GC cells. Our study revealed that miR-497-5p inhibited GC cell proliferation and growth via targeting PDK3.